Association between intrahepatic cccDNA and the severity of liver inflammation in chronic hepatitis B virus infection patients - Zhao, Suxian; Dong, Chen; Chang, Chudi; Zhang, Jiaming; Li, Jing; Zhang, Xiaoxiao; Ren, Weiguang; Zhang, Ying; Nan, Yuemin (Frontiers in Medicine, 2025)
Background and aimsThis research aimed to examine the association between hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) and liver inflammation in chronic hepatitis B (CHB) infection patients.MethodsFrom August 2013 to June 2022, CHB patients at Hebei Medical University Third Hospital (Hebei, China) were recruited. Intrahepatic cccDNA was quantified and its association with liver inflammation was analyzed. Liver inflammation was assessed using the Ishak-modified histological activity index (HAI). Biochemical and viral indicators as well as hepatic inflammation biomarkers were monitored.ResultsIn total, 55 CHB patients were enrolled. The average HBV-cccDNA level was markedly elevated in HBeAg+ patients compared to HBeAg patients. Intrahepatic cccDNA levels differed significantly in different liver inflammation groups and showed a positive correlation with the HAI score for hepatic inflammation.ConclusionHBV-cccDNA level was associated with liver inflammation.